Clinical Experience with the PillCam Patency Capsule prior to Video Capsule Endoscopy: A Real-World Experience. (6th January 2016) - Römmele, C.; Brueckner, J.; Messmann, H.; Gölder, S. K.
Abstract : Background. In patients with known or suspected risk factors for gastrointestinal stenosis, the PillCam patency capsule (PC) is given before a video capsule endoscopy (VCE) in order to minimize the risk of capsule retention (CR). CR is considered unlikely upon excretion of the PC within 30 hours, excretion in an undamaged state after 30 hours, or radiological projection to the colon. Methods. We performed a retrospective analysis of 38 patients with risk factors for CR, who received a PC from 02/2013 to 04/2015 at Klinikum Augsburg. Results. Sixteen of our 38 patients observed a natural excretion after a mean time of 34 hours past ingestion. However, only 8 patients observed excretion within 30 hours, as recommended by the company. In 20 patients passage of the PC into the colon was shown via RFID-scan or radiological imaging (after 33 and 45 hours, resp.). Only 2 patients showed a pathologic PC result. In consequence, 32 patients received the VCE; no CR was observed. Conclusion. Our data indicates that a VCE could safely be performed even if the PC excretion time is longer than 30 hours and the excreted PC was not screened for damage.